Interactive Multimedia Map of Flora and Fauna Distribution in Grade V Social Studies Content for Elementary Schools - Ni Putu Ayu Pravitha Gayatry; I Gusti Agung Ayu Wulandari (Universitas Pendidikan Ganesha, 2025)
The use of interactive learning media in Social Studies (IPS) education remains limited, causing students to experience difficulties in comprehending concepts, particularly regarding the diversity of flora and fauna. This condition impacts students' motivation, understanding, and learning outcomes. This study aims to analyze the effectiveness of interactive multimedia on the distribution map of flora and fauna in enhancing the learning outcomes of fifth-grade elementary school students in Social Studies subjects. The research employed a development method using the ADDIE model (analyze, design, development, implementation, and evaluation). The research subjects consisted of 28 fifth-grade students. Data were collected through interviews, observations, questionnaires, and multiple-choice tests, using validated instruments. Data analysis techniques included descriptive quantitative analysis, descriptive qualitative analysis, and inferential statistical analysis using a t-test. The effectiveness test results showed that the tcalculated value (6.43) was greater than the ttable value (2.05), indicating that H₀ was rejected and H₁ was accepted. These findings confirm that interactive multimedia for flora and fauna distribution maps is effective in improving student learning outcomes. The implications suggest that interactive multimedia can enhance students’ learning motivation, conceptual understanding, and critical thinking skills in connecting lesson content with their surrounding environment.